Change management and leadership within the Reykjavík police department - Júlíana Einarsdóttir 1986- (2016)
This masters thesis attempts to examine the changed management and leadership process at the Reykjavík police department and its effects on women´s job satisfaction, their attitudes towards these changes in management and leadership, and whether the changes have strengthened their position in a male dominant environment. Key practical perspectives are discussed relating to servant leadership and lean management, as well as basic theoretical concepts. The methodological approach was qualitative, where interviews were conducted with seven women within the Reykjavík police department, as well as the commissioner of the department. Results showed that women are satisfied with new management and leadership and their job satisfaction is high. They especially value the characteristics of the new leadership, which are caring, open and motivating. The culture is the main challenge in the change process of the organization, since it is deep rooted and male dominant.